Piezoactuators for Miniature Robots - Simu, Urban (Uppsala universitet, Institutionen för materialvetenskap, 2002)
Challenges in the realisation of a miniature robot are both to handle the complexity of such a system, and to cope with effects of the actual reduction in physical size of all the parts. In particular, the mechanisms for locomotion have to be analysed. The main achievements presented in the thesis are the evaluation and the development of fabrication techniques for miniature multilayer piezoceramic actuators, the evaluation of different motion mechanisms for miniature robots, and the development of building techniques for piezo-based miniature robots. New piezoelectric drive units for miniature robots were designed and fabricated. To realize these monolithic devices, the fabrication technique for multilayer piezoceramic structures was further developed and evaluated with respect to the potential for miniaturisation. Introducing milling in the green state as a technique for shaping piezoceramic actuators gave a geometrical freedom without impairing the possibility of miniaturisation. A rapid prototype process was also developed. In this process, green machining in a milling machine was not only used to shape the multilayer structure, but also to pattern the internal electrodes. The first prototype was a multilayer telescopic actuator, which proved to have a displacement amplification of about 5 compared to a multilayer stack. The drive units were used to evaluate different motion mechanisms. Experiments showed that for a mass corresponding to a typical miniature robot, i.e. 1-10 g, it is possible to use both dynamic and quasistatic motion mechanisms. Artefacts due to vibrations were identified as the main reason for non-ideal behaviour when the movable mass is small. Design criteria for robots with small masses are presented. A tethered cm3 miniature robot for micromanipulation was successfully built. Application specific integrated circuits and two drive units were integrated with a particular building technique. Three-axial positioning and manipulating operations were demonstrated, allowing for a 5-axial movement of a tool.